Novel peripherally substituted metal-free, zinc (II), and cobalt (II) phthalocyanines with 1,1 '-thiobis(2-napthol) and additional tetraphthalonitrile groups: Synthesis, aggregation behavior, electrochemical redox and electrocatalytic oxygen reducing properties - ÖZKAYA, ALİ RIZA; ORMAN, EFE BATURHAN (ELSEVIER SCIENCE SA, 2020)
Novel phthalocyanines containing only 1,1'-thiobis(2-napthol) groups or 1,1'-thiobis(2-napthol) and phthalonitrile groups at peripheral positions were prepared by nucleophilic displacement reaction through cyclotetramerization of phthalonitrile derivatives, benzo[b]dinaphtho [1,2-h:2',1'-e] [1,4,7] dioxathionine-5,6-dicarbonitrile and 4,4'- [thiobis(naphthalene-1,2-diyloxy)] diphthalonitrile in penthanol. The aggregation tendencies and electrochemical redox properties of all phthalocyanines were investigated on the basis of central metal, solvent medium and subsituent effects, using UV-Vis spectral and classical electroanalytical techniques. The compounds exhibited metal-and/or phthalocyanine ring-based electron transfer processes which were coupled by distinct spectral changes and thus, net color transformations pointing out the possibility for their usage in electrochromic applications. Furthermore, remarkable enhancement in catalytic activity towards oxygen reduction and high tolerance to methanol during this reaction have been observed when the zinc (II) or 2H center was replaced with cobalt (II).
Keywords: Phthalocyanine; Aggregation; Electrochemistry; Spectroelectrochemistry; Electrocatalysis; Oxygen reduction; GAS-SENSING PROPERTIES; METALLOPHTHALOCYANINES; REDUCTION; COMPLEXES; ZN(II); NICKEL; CO(II); IRON; BENZYLMERCAPTO; PERFORMANCE